Development Of Marble Maze Media For Training Problem-Solving Skills In Early Childhood - Siagian, Eka Anggraini; Sapri, Sapri (UIN Sultan Maulana Hasanudin Banten, 2025)
The Effect Of The Role play Method On The Ability To Read Poetry Of Third Grade Students Of SDN 117509. The purpose of this research is to investigate the creativity of students in grade III at SDN 117509 and Puldung. Students do not have sufficient skills in reading poetry, including difficulty in finding punctuation features, inappropriate use of punctuation features, and inappropriate intonation when reading poetry. The initial experiment, designed for one group before and after the test, was conducted on 25 grade III students. The multiple-option test method was used to collect data. The results of the study showed that rhetorical games affected students' rhetorical reading skills. The results of the hypothesis test with a t-value of (- 9.914) (1.677), which showed that there was a positive effect and significant comparison on students' poetry reading skills, strengthened our belief that this method was efficient in improving students' poetry reading skills. There was a significant comparison between the results of the pre- and post-tests. Therefore, the findings of this study indicate that positional games can be used as an effective teaching method to improve students' poetry reading skills.